Molding process of cosmetic powder block and cosmetic powder block

By using a specific crosslinked polymer as a binder, the filling process of cosmetic powder blocks is carried out at room temperature, and the quality and performance problems caused by heating filling and cooling and curing in the prior art are solved, and the density, drop resistance and water resistance of cosmetic powder blocks are improved.

CN119908976AActive Publication Date: 2025-05-02SHANGHAI AZ SCIENCE & TECHNOLOGY CO LTD +1

Patent Information

Application Number
CN202510387186.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2025-05-02
Estimated Expiration
2045-03-31

AI Technical Summary

Technical Problem

In the existing cosmetic powder preparation process, the use of thermoreversible polysaccharides requires heating filling and cooling and curing, resulting in the impact of product quality and performance, such as pores, poor drop resistance and poor water resistance.

Method used

Polyacrylate cross-linked polymer-6, sodium polyacryloyldimethyltaurate or ammonium acryloyldimethyltaurate/beanol polyether-25 methacrylate cross-linked polymer is used as the binder to realize filling at a normal temperature of 15~40°C to avoid the high temperature cooling process.

Benefits of technology

The prepared cosmetic powder has good density, excellent drop resistance, a fine relief surface without pores, and has better water resistance and sweat resistance, making it difficult to take off makeup after use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119908976A_ABST
    Figure CN119908976A_ABST
Patent Text Reader

Abstract

The invention discloses a forming process of a cosmetic powder block and the cosmetic powder block. The forming process comprises the following steps: mixing: mixing raw materials of the cosmetic powder block to obtain a mixed material body; filling, namely filling the mixed material body into a mold at the temperature of 15-40 DEG C; demolding and drying; the mixed material body comprises the following components in parts by mass: 0.02-1 part of an adhesive; 20 to 65 parts of powder; 0.5 to 35 parts of emollient; 0.05 to 3 parts of an anti-corrosion component; 0.05 to 4 parts of an emulsifier; 40 to 80 parts of a solvent; the adhesive is prepared from at least one of a polyacrylate cross-linked polymer-6, sodium polyacryloyldimethyl taurate and ammonium acryloyldimethyl taurate / beheneth-25 methacrylate cross-linked polymer. According to the technical scheme, the compact cosmetic powder block can be prepared through a normal-temperature filling technology, air holes are not prone to being generated in the surface of the prepared powder block, excellent compactness and falling resistance are achieved, better water resistance and sweat resistance are achieved, and makeup removal is not prone to occurring.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of cosmetics, and in particular relates to a molding process of a cosmetic powder block and a cosmetic powder block. Background Art

[0002] Powder cosmetics can be in the form of loose powder or dense powder blocks. At present, the formula for making cosmetic powder blocks (especially cosmetic powder blocks with three-dimensional relief patterns on the surface) usually contains thermoreversible polysaccharides (or natural polysaccharides), such as xanthan gum, gellan gum, cellulose and its derivatives. Thermoreversible polysaccharides have the characteristics of dissolving in the water phase when heated and forming a three-dimensional network gel structure after cooling, which can give the powder block a compact texture and prevent the powder from loosening or breaking. After adding a solvent to the formula containing thermoreversible polysaccharides and mixing evenly, the mixed material is gel-like or jelly-like at room temperature and has poor fluidity. It must be heated (usually heated to 50~90℃) to make the material thinner and have better fluidity before it can be poured into the mold. After the filling is completed, the material body is cooled and solidified, demoulded, dried, and finally a cosmetic powder block is obtained.

[0003] Therefore, the formula using thermoreversible polysaccharides will inevitably go through the process of heating filling and cooling solidification, and the entire preparation process cannot be completed at room temperature. However, the above-mentioned heating filling and cooling solidification process will affect the quality and performance of the cosmetic powder block. For example, after the mixed material body is poured into the mold, as the temperature drops from high, the mixed material body quickly thickens, resulting in incomplete filling of the parts with sharp angles in the three-dimensional relief pattern, the appearance of pores, and affecting the appearance and yield of the product. In addition, in the subsequent demoulding and drying steps, the material body may also experience a freezing environment (such as frozen demoulding or freeze drying). During the transition from the high temperature conditions of filling to the freezing conditions of demoulding and drying, the material body shrinks, resulting in poor drop resistance of the cosmetic powder block.

[0004] Meanwhile, a relatively large amount of water-in-oil emulsifier needs to be added to the above-mentioned cosmetic powder block formula to make the mixed material body a stable emulsified system. However, the addition of a relatively large amount of water-in-oil emulsifier results in the cosmetic powder block product having poor water resistance after molding, and the experience presented to consumers is that the product has poor makeup-lasting and sweat-resistant properties and is easy to fall off. Summary of the invention

[0005] In order to solve the above problems, the present application provides a cosmetic powder block molding process and a cosmetic powder block. The cosmetic powder block prepared according to the molding process of the present application not only has good density, excellent anti-drop performance, and a fine relief surface without pores, but also has better water resistance and sweat resistance, and is not easy to come off after use.

[0006] The first aspect of the present application provides a cosmetic powder block molding process, comprising: Mixing, including mixing the raw materials of the cosmetic powder block to obtain a mixed material body; Filling, including filling the mixed material into the mold at 15-40°C; Demolding and drying to obtain a cosmetic powder block; The mixed material includes the following components in parts by mass: Adhesive: 0.02~1 parts; Powder: 20~65 parts; Emollient: 0.5~35 parts; Preservative component: 0.05~3 parts; Emulsifier: 0.05~4 parts; Solvent: 40~80 parts; The adhesive comprises at least one of polyacrylate cross-linked polymer-6, sodium polyacryloyldimethyl taurate, and ammonium acryloyldimethyl taurate / behenyl alcohol polyether-25 methacrylate cross-linked polymer.

[0007] Without intending to be limited by any theory or explanation, the inventors have found that the use of polyacrylate cross-linked polymer-6, sodium polyacryloyldimethyl taurate or ammonium acryloyldimethyl taurate / behenyl alcohol polyether-25 methacrylate cross-linked polymer instead of natural polysaccharides can make the mixed material body have good fluidity under natural ambient temperature conditions of 15~40°C, and filling can be completed without heating; at the same time, after the material body is dried and formed, it can also give the powder block a compact texture to prevent the powder from loosening or breaking. Compared with the prior art, the technical solution provided by the present application can realize the preparation of dense cosmetic powder blocks by normal temperature and pressure filling process. According to the molding process of the present application, the temperature of the mixed material body is the same as or close to the ambient temperature, and the mixed material body poured into the mold will not experience the process of poor fluidity due to the temperature decreasing from high to low, so there is sufficient time to fill into the three-dimensional relief pattern and discharge the air in the sharp angle part of the pattern, thereby significantly reducing the risk of pores, and the prepared cosmetic powder block can present an excellent fine relief surface. At the same time, filling at natural ambient temperature also avoids the adverse effects of different shrinkage rates of various material components during high temperature cooling on the anti-drop performance of the cosmetic powder block, thereby effectively improving the anti-drop performance of the cosmetic powder block. In addition, since there is no high temperature process in the entire preparation process of the cosmetic powder block, active substances that will be inactivated or partially inactivated at high temperatures, such as polypeptide active substances, astaxanthin, vitamin A alcohol, etc., can be added to the cosmetic powder block, which can improve the designability of the cosmetic powder block formula.

[0008] In addition, the inventors surprisingly found that the use of polyacrylate cross-linked polymer-6, sodium polyacryloyldimethyl taurate or ammonium acryloyldimethyl taurate / behenyl alcohol polyether-2 methacrylate cross-linked polymer instead of natural polysaccharides can also improve the stability of the emulsified system of the mixed material. Therefore, only a small amount of water-in-oil emulsifier needs to be added to the formula of the cosmetic powder block to achieve a very stable emulsification effect. In this way, the cosmetic powder block can have better water resistance, improve the makeup holding and sweat resistance of the cosmetic powder block, and achieve the effect of not being easy to remove makeup.

[0009] In any embodiment of the present application, the binder includes polyacrylate cross-polymer-6.

[0010] In any embodiment of the present application, the mass fraction of the emulsifier is less than or equal to 4% of the total mass fraction of the mixture; preferably, the mass fraction of the emulsifier is less than or equal to 1% of the total mass fraction of the mixture.

[0011] In any embodiment of the present application, the mass percentage of the solvent in the cosmetic powder block is less than 5%, preferably less than 1%.

[0012] In any embodiment of the present application, the filling includes filling the mixed material body into a mold at 15-40° C. under normal pressure.

[0013] In any embodiment of the present application, demoulding and drying include: drying after demoulding, or demoulding after drying.

[0014] In any embodiment of the present application, drying includes at least one of freeze drying, microwave drying, heating drying, vacuum drying and supercritical fluid drying.

[0015] In any embodiment of the present application, before demoulding and drying, the molding process further includes pre-curing and / or pre-drying.

[0016] In any embodiment of the present application, pre-curing includes freeze-curing the mixed material body after filling.

[0017] In any embodiment of the present application, freezing and solidifying the filled mixed material body includes: placing the mixed material body in an environment of -120~0°C to solidify the mixed material body.

[0018] In any embodiment of the present application, freezing and solidifying the filled mixed material body includes: placing the mixed material body in a liquid nitrogen tunnel at -120~-70°C to solidify the mixed material body.

[0019] In any embodiment of the present application, the mixed material body is placed in a liquid nitrogen tunnel at -120~-70°C to solidify the mixed material body, and then demolding and drying include: demolding the solidified mixed material body and then freeze-drying the demolded material body; or freeze-drying the solidified mixed material body and then demolding the freeze-dried material body.

[0020] In any embodiment of the present application, pre-drying includes the step of removing part of the solvent from the mixed material body after filling.

[0021] In any embodiment of the present application, the step of removing part of the solvent from the mixed material body after filling includes one or more of heating drying, microwave drying, vacuum drying, supercritical fluid drying, filter pressing, and suction.

[0022] In any embodiment of the present application, the powder is selected from at least one of mica, synthetic fluorphlogopite, talc, silica, boron nitride, bismuth oxychloride, barium sulfate, aluminum oxide, potassium sodium aluminum silicate, calcium aluminum borosilicate, sodium calcium borosilicate, starch and its derivatives, plastic microbeads and colorants.

[0023] In any embodiment of the present application, the emollient is selected from at least one of animal and plant oils and their derivatives, silicone oil and synthetic oil.

[0024] In any embodiment of the present application, the preservative component is selected from at least one of phenoxyethanol, parabens, chlorphenesin, potassium sorbate, sodium benzoate, caprylyl glycol, p-hydroxyacetophenone, ethylhexylglycerin, 1,2-hexanediol, caprylhydroxamic acid, 1,2-pentanediol, glyceryl caprylate and cymene.

[0025] In any embodiment of the present application, the emulsifier is selected from an emulsifier having a hydrophilic-lipophilic balance (HLB value) greater than 6; the emulsifier having an HLB value greater than 6 is preferably selected from at least one of Tween 20, Tween 40, Tween 60, Tween 80, PEG-12 polydimethylsiloxane, polyglyceryl-10 myristate, polyglyceryl-10 laurate and polyglyceryl-10 dioleate.

[0026] In any embodiment of the present application, the solvent is selected from water or a mixture of water and an organic solvent; In any embodiment of the present application, the organic solvent is preferably at least one selected from ethanol, isopropanol, butanol and polyols.

[0027] In any embodiment of the present application, the mold is made of silicone, rubber or metal; optionally, the rubber may include at least one of TPR, TPE, silicone rubber and natural rubber.

[0028] In any embodiment of the present application, the mold includes at least one cavity with an opening; optionally, the bottom of the cavity has a three-dimensional pattern.

[0029] In any embodiment of the present application, the mixed material body further includes an active substance, and the active substance includes a high temperature sensitive active substance and / or a high temperature insensitive active substance.

[0030] Optionally, the mixed material includes high temperature sensitive active substances, for example, at least one of high temperature sensitive active substances such as polypeptide active substances, astaxanthin, vitamin A alcohol, etc.

[0031] A second aspect of the present application provides a cosmetic powder block, which is prepared by the cosmetic powder block molding process of any embodiment of the first aspect. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 It is a schematic diagram of the water resistance test of the cosmetic powder block powder of Example 1 and Comparative Example 5 of the present application; Figure 2 This is a graph showing the water resistance test results of the cosmetic powder blocks of Example 1 and Comparative Example 5 of the present application. DETAILED DESCRIPTION

[0033] In order to make the application purpose, technical solution and beneficial technical effect of the present application clearer, the present application is further described in detail in conjunction with the embodiments below. It should be understood that the embodiments described in this specification are only for explaining the present application, not for limiting the present application.

[0034] For simplicity, this application only explicitly discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an unclearly recorded range; and any lower limit can be combined with other lower limits to form an unclearly recorded range, and any upper limit can be combined with any other upper limit to form an unclearly recorded range. In addition, although not clearly recorded, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unclearly recorded range.

[0035] In the description of the present application, it should be noted that, unless otherwise specified, “above” and “below” are inclusive of the number, and the “multiple” in “one or more” means two or more than two.

[0036] The above application content of the present application is not intended to describe each disclosed embodiment or each implementation in the present application. The following description more specifically illustrates exemplary embodiments. In many places throughout the application, guidance is provided by a series of examples, which can be used in various combinations. In each example, enumeration is only used as a representative group and should not be interpreted as exhaustive.

[0037] As described in the background art, the related technologies all use thermoreversible polysaccharides (or natural polysaccharides) as adhesives and adopt a heated filling molding process to prepare cosmetic powder blocks. After the mixed material is poured into the mold, as the temperature drops from high, the mixed material quickly thickens, resulting in incomplete filling of the parts with sharp angles in the three-dimensional relief pattern, the appearance of pores, and affecting the appearance and yield of the product. In addition, in the subsequent demoulding and drying steps, the material may also experience a freezing environment (such as frozen demoulding or freeze drying). During the transition from the high temperature conditions of filling to the freezing conditions of demoulding and drying, the material shrinks, resulting in poor drop resistance of the cosmetic powder block.

[0038] At the same time, the current formula of cosmetic powder blocks contains a large amount of water-in-oil emulsifier, which results in the cosmetic powder block products after molding not having good water resistance. The experience presented to consumers is that the product's long-lasting and sweat-resistant properties are not good enough, and the makeup is easy to come off.

[0039] In view of this, the inventors, after in-depth research and a large number of experiments, provide a molding process for a cosmetic powder block and a cosmetic powder block.

[0040] A first aspect of the present application provides a cosmetic powder block molding process, comprising steps S10 to S30.

[0041] S10, mixing materials, including mixing raw materials of the cosmetic powder block to obtain a mixed material body.

[0042] S20, filling, includes filling the mixed material into a mold at 15-40°C.

[0043] In step S20, 15-40°C may represent the temperature of the mixture. Exemplarily, the temperature of the mixture may be the same as the ambient temperature, for example, the raw materials of the cosmetic powder block may be mixed in a natural temperature environment of 15-40°C to obtain the mixture, which is then filled.

[0044] S30, demoulding and drying to obtain a cosmetic powder block.

[0045] In step S30, the order of demoulding and drying is not limited, and demoulding can be performed first and then drying, or drying can be performed first and then demoulding, as long as a cosmetic powder block with a predetermined shape and a solvent content lower than a preset standard can be obtained.

[0046] The mixed material includes the following components in parts by mass: Adhesive: 0.02~1 parts; Powder: 20~65 parts; Emollient: 0.5~35 parts; Preservative component: 0.05~3 parts; Emulsifier: 0.05~4 parts; Solvent: 40~80 parts.

[0047] The adhesive comprises at least one of polyacrylate crosspolymer-6, sodium polyacryloyldimethyl taurate, and ammonium acryloyldimethyl taurate / beheneth-25 methacrylate crosspolymer.

[0048] The antiseptic component mentioned above includes an antiseptic, or further includes an antiseptic synergist based on the antiseptic.

[0049] Without intending to be limited by any theory or explanation, the inventors have found that the use of polyacrylate cross-linked polymer-6, sodium polyacryloyldimethyl taurate or ammonium acryloyldimethyl taurate / behenyl alcohol polyether-25 methacrylate cross-linked polymer instead of natural polysaccharides can make the mixed material body have good fluidity under natural ambient temperature conditions of 15~40°C, and filling can be completed without heating; at the same time, after the material body is dried and formed, it can also give the powder block a compact texture to prevent the powder from loosening or breaking. Compared with the prior art, the technical solution provided by the present application can realize the preparation of dense powder blocks by normal temperature and pressure filling process. According to the molding process of the present application, the temperature of the mixed material body is the same as or close to the ambient temperature, and the mixed material body poured into the mold will not experience the process of poor fluidity due to the temperature decreasing from high to low, so there is sufficient time to fill into the three-dimensional relief pattern and discharge the air in the sharp angle part of the pattern, thereby significantly reducing the risk of pores, and the prepared cosmetic powder block can present an excellent fine relief surface. At the same time, filling at natural ambient temperature also avoids the adverse effects of different shrinkage rates of various material components during high temperature cooling on the anti-drop performance of the cosmetic powder block, thereby effectively improving the anti-drop performance of the cosmetic powder block. In addition, since there is no high temperature process in the entire preparation process of the cosmetic powder block, active substances that will be inactivated or partially inactivated at high temperatures, such as polypeptide active substances, astaxanthin, vitamin A alcohol, etc., can be added to the cosmetic powder block, thereby improving the designability of the cosmetic powder block formula.

[0050] In addition, the inventors surprisingly found that the use of polyacrylate cross-linked polymer-6, sodium polyacryloyldimethyl taurate or ammonium acryloyldimethyl taurate / behenyl alcohol polyether-2 methacrylate cross-linked polymer instead of natural polysaccharides can also improve the stability of the emulsified system of the mixed material. Therefore, only a small amount of water-in-oil emulsifier needs to be added to the formula of the cosmetic powder block to achieve a very stable emulsification effect. In this way, the cosmetic powder block can have better water resistance, improve the makeup holding and sweat resistance of the cosmetic powder block, and achieve the effect of not being easy to remove makeup.

[0051] In some embodiments, the binder may include polyacrylate crosspolymer-6.

[0052] Thereby, the fluidity of the mixed material body at natural ambient temperature can be improved more significantly.

[0053] In some embodiments, the mass fraction of the emulsifier may be less than or equal to 4% of the total mass fraction of the mixture; in other embodiments, the mass fraction of the emulsifier may be less than or equal to 1% of the total mass fraction of the mixture. For example, based on the total mass fraction of the mixture as 100%, the amount of the emulsifier may be 4%, 3.5%, 3%, 2.5%, 2%, 1.5%, 1%, 0.8%, 0.5%, 0.2%, 0.15%, 0.05%, or within the range formed by any two of the above values.

[0054] Therefore, the amount of emulsifier used can be further reduced while maintaining the stability of the emulsified system of the mixed material, thereby further improving the water resistance and sweat resistance of the cosmetic powder block, and further improving the makeup durability of the cosmetic powder block.

[0055] In some embodiments, the weight percentage of the solvent in the cosmetic powder block is less than 5%.

[0056] In some embodiments, the weight percentage of the solvent in the cosmetic powder block is less than 1%.

[0057] In some embodiments, the filling step includes filling the mixture into a mold at 15-40°C under normal pressure. Normal pressure can be understood as standard atmospheric pressure (101.325 kPa) or close to standard atmospheric pressure. In this application, normal pressure filling can also be understood as gravity filling, that is, using the self-gravity of the mixture to make the mixture flow into the mold without external pressure assistance.

[0058] In some embodiments, demolding and drying may include: demolding first and then drying.

[0059] In some other embodiments, demoulding and drying may include: drying first and then demoulding.

[0060] According to the above embodiment, the order of demoulding and drying is variable. As an example, the mold containing the mixed material body can be frozen to shape the mixed material body, then demoulded, and dried to the finished product standard to obtain a cosmetic powder block. As another example, the mixed material body in the mold can be dried to the finished product standard, then demoulded to obtain a cosmetic powder block. Those skilled in the art can select the appropriate order and method of demoulding and drying according to actual needs, such as the properties of the mixed material body, the requirements for the degree of drying, process conditions, costs and other factors, which are not limited here.

[0061] In some embodiments, drying may include at least one of freeze drying, microwave drying, heat drying, vacuum drying, and supercritical fluid drying.

[0062] The freeze drying is a drying method in which a water-containing material is frozen below the freezing point to convert water into ice, and then the ice is converted into steam under a relatively high vacuum degree for removal.

[0063] The microwave drying is a drying method that utilizes electromagnetic waves as a heating source and the dried material itself as a heating element.

[0064] The above-mentioned heating drying is a drying method that achieves drying by heating the material.

[0065] The above-mentioned vacuum drying refers to a drying method in which the material is placed under negative pressure conditions and appropriately heated to reach the boiling point under the negative pressure state or the material is solidified by cooling and then dried.

[0066] The supercritical fluid drying is a drying method that utilizes the high solubility of a supercritical solvent to remove the solvent contained in a porous solid to achieve drying.

[0067] The present application may select one drying method or a combination of several drying methods, as long as the purpose of drying can be achieved, and is not limited here.

[0068] In some embodiments, the molding process may further include pre-curing and / or pre-drying before demolding and drying.

[0069] In some embodiments, the pre-curing includes freeze-curing the filled mixed material body.

[0070] In some embodiments, the filled mixed material body is freeze-cured, which may specifically include: placing the mixed material body in an environment of -120 to 0° C. to solidify the mixed material body.

[0071] Preferably, in some embodiments, the filled mixed material body is subjected to freeze solidification, which may specifically include: placing the mixed material body in a liquid nitrogen tunnel at -120~-70°C for low-temperature freezing treatment to solidify the mixed material body.

[0072] In some embodiments, the mixed material body can be placed in a liquid nitrogen tunnel at -120~-70°C for low-temperature freezing treatment to solidify the mixed material body, and then the following demolding and drying steps can be performed: demolding the solidified mixed material body, and then freeze-drying the demolded material body; or freeze-drying the solidified mixed material body, and then demolding the freeze-dried material body.

[0073] In some embodiments, pre-drying includes the step of removing part of the solvent from the mixed material body after filling.

[0074] In some embodiments, the step of removing part of the solvent from the mixed material after filling includes one or more of heating drying, microwave drying, vacuum drying, supercritical fluid drying, filter pressing, and suction.

[0075] In the present application, powders, emollients, preservative components, emulsifiers and solvents can be selected from materials known in the art. Those skilled in the art can select appropriate types of powders, emollients, preservative components, emulsifiers and solvents according to the needs of the product, and there is no limitation here.

[0076] In some embodiments, the powder can be selected from at least one of mica, synthetic fluorphlogopite, talc, silica, boron nitride, bismuth oxychloride, barium sulfate, aluminum oxide, sodium potassium aluminum silicate, calcium aluminum borosilicate, calcium sodium borosilicate, starch and its derivatives, plastic microbeads and colorants.

[0077] In some embodiments, the emollient may be selected from at least one of plant and animal oils and their derivatives, silicone oils, and synthetic oils.

[0078] In some embodiments, the preservative component can be selected from at least one of phenoxyethanol, parabens, chlorphenesin, potassium sorbate, sodium benzoate, caprylyl glycol, p-hydroxyacetophenone, ethylhexylglycerin, 1,2-hexanediol, caprylhydroxamic acid, 1,2-pentanediol, glyceryl caprylate and cymene.

[0079] In some embodiments, the emulsifier may be selected from emulsifiers having an HLB value greater than 6.

[0080] Preferably, in some embodiments, the emulsifier having an HLB value greater than 6 may be selected from at least one of Tween 20, Tween 40, Tween 60, Tween 80, PEG-12 polydimethylsiloxane, polyglyceryl-10 myristate, polyglyceryl-10 laurate and polyglyceryl-10 dioleate.

[0081] In some embodiments, the solvent may be selected from water or a mixture of water and an organic solvent.

[0082] Preferably, in some embodiments, the organic solvent may be selected from at least one of ethanol, isopropanol, butanol and polyols.

[0083] In some embodiments, the mold may be made of silicone, rubber, or metal.

[0084] In some embodiments, the rubber may include at least one of TPR, TPE, silicone rubber, and natural rubber.

[0085] In some embodiments, the mold may include at least one cavity having an opening.

[0086] In the mold, the cavity can be used to accommodate the mixed material body. Specifically, the mold can be placed so that the opening of the cavity is upward, and the mixed material body is filled into the cavity through the opening, and the mold is demolded after pre-curing and / or pre-drying, and then further dried, or directly dried after filling, to form a cosmetic powder block with a specific shape. It is understood that a mold can include one or more cavities for preparing one or more cosmetic powder blocks. Each cavity has at least one opening for filling and demoulding.

[0087] The inner wall of the chamber may or may not have a three-dimensional pattern.

[0088] In some embodiments, the bottom of the chamber may have a three-dimensional pattern, so that the cosmetic powder block product can be formed with a fine relief surface, thereby improving the visual effect of the product.

[0089] In some embodiments, the mixed material body may further include an active substance, which may include an active substance that is sensitive to high temperatures and / or an active substance that is not sensitive to high temperatures.

[0090] Since the molding process provided in the present application does not go through a high temperature process, in some embodiments, the mixed material body may contain active substances that are sensitive to high temperatures or even easily inactivated at high temperatures. In some examples, the above-mentioned high temperature sensitive active substances may include substances that change in properties or lose activity at temperatures above 50°C (e.g., 50°C to 90°C), and these high temperature sensitive active substances may include, for example, at least one of polypeptide active substances, astaxanthin, and vitamin A alcohol.

[0091] A second aspect of the present application provides a cosmetic powder block, which is prepared by the cosmetic powder block molding process of any embodiment of the first aspect.

[0092] The cosmetic powder block of the present application is prepared by the cosmetic powder block molding process of any embodiment of the first aspect. Therefore, the cosmetic powder block not only has good density, excellent anti-drop performance, and a fine embossed surface without pores, but also has better water resistance and sweat resistance, and is not easy to come off after use.

[0093] Example The following examples describe the disclosure of the present invention in more detail, and these examples are intended for illustrative purposes only, as various modifications and variations within the scope of the disclosure of the present invention will be apparent to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.

[0094] Example 1 The cosmetic powder block of Example 1 is prepared by the following steps (1) to (4).

[0095] (1) Mixing: Mix the raw materials in the formula shown in Table 1 at 20° C. to obtain a mixed material. As shown in Table 1, the binder in the raw materials of Example 1 is 0.15 parts by weight of polyacrylate cross-linked polymer-6, and the water-in-oil emulsifier is 0.15 parts by weight of Tween 60.

[0096] (2) Filling: The mixed material is filled at 20°C so that the mixed material flows into the silicone mold by its own gravity without external pressure assistance. The silicone mold has an upwardly open cavity and a three-dimensional pattern at the bottom of the cavity, which is used to form a three-dimensional relief pattern on the surface of the cosmetic powder block.

[0097] (3) Demolding: The mixed material in the mold is ultra-low temperature pre-frozen in a liquid nitrogen tunnel to solidify the mixed material. The temperature inside the liquid nitrogen tunnel is -70°C, and the mixed material passes through the liquid nitrogen tunnel for 10 minutes. After the mixed material is solidified, demolding is completed to obtain a master product.

[0098] (4) Drying: The mother product after demoulding is freeze-dried until the mass percentage of the solvent is less than 1%, thereby obtaining a cosmetic powder block.

[0099] Table 1

[0100] Example 2 The cosmetic powder block of Example 2 was prepared according to the formula shown in Table 2. As shown in Table 2, compared with Example 1, Example 2 still used polyacrylate cross-linked polymer-6 as a binder, but the mass portion of polyacrylate cross-linked polymer-6 was 0.04 parts, the mass portion of water-in-oil emulsifier Tween 60 was 0.5 parts, and the other raw materials and contents were also different.

[0101] The preparation steps of the cosmetic powder block of Example 2 are substantially the same as those of Example 1, except that the mixing and filling temperature of Example 2 is adjusted to 15°C.

[0102] Table 2

[0103] Example 3 The cosmetic powder block of Example 3 was prepared according to the formula shown in Table 3. As shown in Table 3, compared with Example 1, Example 3 still used polyacrylate cross-linked polymer-6 as a binder, but the mass portion of polyacrylate cross-linked polymer-6 was 0.3 parts, the mass portion of water-in-oil emulsifier Tween 60 was 0.05 parts, and the other raw materials and contents were also different.

[0104] The preparation steps of the cosmetic powder block of Example 3 are substantially the same as those of Example 1, except that the mixing and filling temperature of Example 3 is adjusted to 30°C.

[0105] Table 3

[0106] Example 4 The cosmetic powder block of Example 4 was prepared according to the formula shown in Table 4. As shown in Table 4, compared with Example 1, Example 4 still used polyacrylate cross-linked polymer-6 as a binder, but the mass portion of polyacrylate cross-linked polymer-6 was 0.8 parts, the oil-in-water emulsifier was replaced by 0.3 mass portions of PEG-12 polydimethylsiloxane, and the other raw materials and contents were also different.

[0107] The preparation steps of the cosmetic powder block of Example 4 are substantially the same as those of Example 1, except that the mixing and filling temperature of Example 4 is adjusted to 40°C.

[0108] Table 4

[0109] Example 5 The cosmetic powder block of Example 5 was prepared according to the formula shown in Table 5. As shown in Table 5, compared with Example 1, Example 5 used sodium polyacryloyldimethyl taurate as a binder, and other raw materials and contents were the same as those of Example 1.

[0110] The preparation steps of the cosmetic powder block of Example 5 are also the same as those of Example 1.

[0111] Table 5

[0112] Example 6 The cosmetic powder block of Example 6 was prepared according to the formula shown in Table 6. As shown in Table 6, compared with Example 1, Example 6 used ammonium acryloyldimethyltaurate / beheneth-25 methacrylate cross-linked polymer as a binder, and other raw materials and contents were the same as those of Example 1.

[0113] The preparation steps of the cosmetic powder block of Example 6 are also the same as those of Example 1.

[0114] Table 6

[0115] Example 7 The raw materials and contents of the cosmetic powder block in Example 7 are the same as those in Example 1.

[0116] The preparation steps of the cosmetic powder block of Example 7 are substantially the same as those of Example 1, except that the freeze drying in the drying step is replaced by heating drying at 40°C.

[0117] Example 8 The raw materials and contents of the cosmetic powder block of Example 8 are the same as those of Example 1. The preparation steps of Example 8 are basically the same as those of Example 1, except that after filling, the mixed material is first subjected to microwave drying to remove part of the moisture, and then the same demoulding and drying steps as those of Example 1 are performed.

[0118] Example 9 The cosmetic powder block of Example 9 was prepared according to the formula shown in Table 7. As shown in Table 7, Example 9 used sodium polyacryloyldimethyl taurate as a binder.

[0119] The preparation steps of the cosmetic powder block of Example 9 are the same as those of Example 1.

[0120] Table 7

[0121] Example 10 The cosmetic compact of Example 10 was prepared according to the formula shown in Table 8. As shown in Table 8, Example 10 used ammonium acryloyldimethyltaurate / steareth-25 methacrylate crosspolymer as a binder.

[0122] The preparation steps of the cosmetic powder block of Example 10 are the same as those of Example 1.

[0123] Table 8

[0124] Embodiment 11 The cosmetic powder block of Example 11 was prepared according to the formula shown in Table 9. As shown in Table 9, Example 11 used sodium polyacryloyldimethyl taurate as a binder.

[0125] The preparation steps of the cosmetic powder block of Example 11 are substantially the same as those of Example 1, except that the mixing and filling temperature is 30°C.

[0126] Table 9

[0127] Example 12 The cosmetic compact of Example 12 was prepared according to the formula shown in Table 10. As shown in Table 10, Example 12 used ammonium acryloyldimethyltaurate / steareth-25 methacrylate crosspolymer as a binder.

[0128] The preparation steps of the cosmetic powder block of Example 12 are basically the same as those of Example 1, except that the mixing and filling temperature is 35°C.

[0129] Table 10

[0130] Comparative Example 1 The cosmetic powder block of Comparative Example 1 was prepared according to the formula shown in Table 11. As shown in Table 11, compared with Example 1, Comparative Example 1 used thermoreversible polysaccharide gellan gum instead of polyacrylate crosslinked polymer-6 as a binder, and potassium chloride was additionally added (the combination of thermoreversible polysaccharide and potassium chloride is commonly used in the prior art, and can enhance the colloidal network structure formed by the polysaccharide based on ionic crosslinking); accordingly, the amount of deionized water in Comparative Example 1 was reduced to 42.45 parts by mass. Other raw materials and contents were the same as those in Example 1.

[0131] The preparation steps of the cosmetic powder block of Comparative Example 1 are also the same as those of Example 1.

[0132] Table 11

[0133] Comparative Example 2 The cosmetic powder block of Comparative Example 2 was prepared according to the formula shown in Table 12. As shown in Table 12, compared with Example 4, Comparative Example 2 used the thermoreversible polysaccharide Chondrus crispus instead of polyacrylate cross-linked polymer-6 as a binder, and potassium chloride used in combination with the thermoreversible polysaccharide was additionally added. Accordingly, the amount of deionized water used in Comparative Example 2 was reduced to 47.15 parts by mass. Other raw materials and contents were the same as those in Example 4.

[0134] The preparation steps of the cosmetic powder block of Comparative Example 2 are also the same as those of Example 4.

[0135] Table 12

[0136] Comparative Example 3 The formula composition of Comparative Example 3 is the same as that of Comparative Example 1. The preparation steps of Comparative Example 3 are substantially the same as those of Comparative Example 1, except that the mixing and filling of Comparative Example 3 are performed at 80°C.

[0137] Comparative Example 4 The cosmetic powder block of Comparative Example 4 was prepared according to the formula shown in Table 13. As shown in Table 13, the formula composition of Comparative Example 4 differs from that of Comparative Example 3 only in that the amount of emulsifier Tween 60 is increased to 2.15 parts by mass, and the amount of deionized water is reduced to 40.45 parts by mass. The preparation steps of Comparative Example 4 are the same as those of Comparative Example 3, and the mixing and filling are performed at 80°C.

[0138] Table 13

[0139] Comparative Example 5 The cosmetic powder block of Comparative Example 5 was prepared according to the formula shown in Table 14. As shown in Table 14, the raw materials of Comparative Example 5 used thermoreversible polysaccharide gellan gum and potassium chloride used in combination with thermoreversible polysaccharide, and compared with the formula composition of Comparative Example 4, the formula of Comparative Example 5 further increased the amount of emulsifier Tween 60 to 5 parts by mass, and correspondingly reduced the amounts of deionized water and squalane.

[0140] The preparation steps of the cosmetic powder block of Comparative Example 5 are substantially the same as those of Comparative Examples 3 and 4, and the mixing and filling are performed at 80°C.

[0141] Table 14

[0142] Comparative Example 6 The cosmetic powder block of Comparative Example 6 was prepared according to the formula shown in Table 15. As shown in Table 15, compared with Example 1, Comparative Example 6 used hydroxyethyl acrylate / sodium acryloyldimethyl taurate copolymer instead of polyacrylate crosslinked polymer-6 as a binder, and other raw materials and contents were the same as those in Example 1.

[0143] The preparation steps of the cosmetic powder block of Comparative Example 6 are also the same as those of Example 1.

[0144] Table 15

[0145] Comparative Example 7 The cosmetic powder block of Comparative Example 7 was prepared according to the formula shown in Table 16. As shown in Table 16, compared with Example 1, Comparative Example 7 used sodium polyacrylate instead of polyacrylate cross-linked polymer-6 as a binder, and other raw materials and contents were the same as those in Example 1.

[0146] The preparation steps of the cosmetic powder block of Comparative Example 7 are also the same as those of Example 1.

[0147] Table 16

[0148] Test Section (1) Observe the fluidity, gravity filling feasibility and emulsification stability of the mixture.

[0149] (2) Observe whether there are pores at the sharp angles of the three-dimensional relief pattern on the surface of the powder block.

[0150] (3) Water resistance test of cosmetic powder like Figure 1 As shown, the cosmetic powder blocks of Example 1 and Comparative Example 5 were directly taken with fingertips and applied to the arm. Then, they were rinsed under the tap for 1 minute and the powder residue was observed. The test results are shown in FIG. Figure 2 shown.

[0151] (4) Sweat resistance test 30 female volunteers with an average age of 35±1.5 years old were selected to provide the cosmetic powder blocks of the above embodiment and comparative example for trial use. After 1 hour in a hot and humid environment at 35°C, the anti-perspiration performance of the products was scored. The score ranged from 1 to 5 points, and the scoring criteria were as follows: 1 point - very dissatisfied with the anti-sweat property; 2 points - dissatisfied with the anti-sweat property; 3 points - considered the anti-sweat property to be average; 4 points - relatively satisfied with the anti-sweat property; 5 points - very satisfied with the anti-sweat property.

[0152] The average value of the scoring results of 30 volunteers was recorded as the anti-perspiration score of the cosmetic powder block of each embodiment and comparative example.

[0153] (5) Drop resistance test Adjust the rotating screws on the drop test table and adjust the flat plate to the 30cm scale; place the powder block with the front side facing up in the center of the test height.

[0154] Perform the first drop test: Press the test bench button to let the powder block fall onto the hard board surface, pick up the powder block that has fallen onto the surface, and check whether the powder block surface is cracked or broken. If the powder block is cracked or broken, stop the drop test for this powder block. If the powder block is normal, then perform the second drop test. The operation steps for the second drop test are the same as the first drop test. If the powder block is cracked or broken, then stop the drop test for this powder block; if the powder block is normal, then perform the third drop test. The operation steps for the third drop test are the same as the first drop test.

[0155] The ratio of the number of powder cakes that broke in each drop test to the total number of powder cakes that were dropped in the drop test is the breakage rate of each drop test. The first breakage rate, the second breakage rate, and the third breakage rate of Examples 1 to 12 and Comparative Examples 1 to 7 are recorded respectively. The sum of the three breakage rates is used to score the drop resistance. The scoring rules for drop resistance are as follows: Table 17

[0156] The test results of test items (1), (2), (4) and (5) of each embodiment and comparative example are shown in Table 18.

[0157] Table 18

[0158] In Table 18, " / " may indicate that the corresponding test was not performed. For example, the materials of Comparative Examples 1-4 and Comparative Examples 6-7 were demulsified, and a uniform cosmetic powder block could not be successfully prepared, so the cosmetic powder block appearance test, sweat resistance test, and drop resistance test could not be performed.

[0159] It can be found from the test results of Table 18 that in the cosmetic powder block forming process of Examples 1 to 12, by introducing a specific adhesive into the formula of the cosmetic powder block, the mixed material body has good fluidity at room temperature, without heating or external pressure assistance, and can be filled at room temperature and pressure. The surface of the prepared powder block presents a perfect relief, and there are no pores even in the sharp angle part. The cosmetic powder blocks prepared in Examples 1 to 12 also have good density and anti-drop performance. Among them, the amount of adhesive used in Examples 2, 9, 11, and 12 is relatively low, so it has a certain impact on the anti-drop performance, but the anti-drop score of 4 points is also within an acceptable range. Example 7 uses 40°C heating and drying, and the cosmetic powder block has a little shrinkage phenomenon, but it can still maintain good anti-drop performance. The cosmetic powder blocks of the remaining examples did not have material shrinkage, and the anti-drop scores were all 5 points, showing excellent anti-drop performance.

[0160] In addition, in Examples 1 to 12, when the amount of emulsifier used was low, the material body could maintain a delicate and uniform state without demulsification, successfully completing the preparation of the cosmetic powder block, and successfully avoiding the adverse effect of adding too much water-in-oil emulsifier on the water resistance of the cosmetic powder block. The cosmetic powder blocks prepared in Examples 1 to 12 all showed good anti-sweat performance. Among them, the amount of emulsifier used in Example 12 was slightly high, resulting in a slight decrease in the anti-sweat score.

[0161] In contrast, Comparative Example 1 uses thermoreversible polysaccharide gellan gum as a binder, and the mixed material is jelly-like at room temperature and cannot be filled at normal pressure; and gellan gum cannot improve the stability of the emulsified system of the material. Therefore, when the amount of emulsifier is the same as that of Example 1, the material of Comparative Example 1 breaks the emulsion, and a cosmetic powder block with uniform and fine texture cannot be prepared.

[0162] Similarly, in Comparative Example 2, the thermoreversible polysaccharide Chondrus crispus was used as a binder, and the mixed material was jelly-like at room temperature and could not be filled at normal pressure. When the amount of emulsifier was the same as that in Example 4, the material of Comparative Example 2 also showed demulsification, and a cosmetic powder block with a uniform and fine texture could not be produced.

[0163] Comparative Example 3 also uses gellan gum as a binder, and the formula composition is the same as that of Comparative Example 1, and the mixed material is heated to 80° C. Although the fluidity of the material is significantly improved under heating, stratification and demulsification occur inside the material, and a cosmetic powder block with uniform and fine texture cannot be prepared, indicating that the amount of emulsifier in the formula is insufficient.

[0164] Compared with Comparative Example 3, the formula composition of Comparative Example 4 increases the amount of emulsifier Tween 60 to 2.15 parts by mass. Although the fluidity of the material body is significantly improved under heating, stratification and demulsification still occur inside the material body, and a cosmetic powder block with uniform and fine texture cannot be prepared, indicating that the amount of emulsifier in the formula is still insufficient.

[0165] Comparative Example 5 is based on Comparative Example 4, and the amount of emulsifier Tween 60 is further increased to 5 parts by mass. When mixing and filling are carried out at 80°C, the fluidity of the material is relatively high, and normal pressure filling can be successfully completed. In addition, due to the increase in the amount of emulsifier, a delicate and uniform material is obtained, and no demulsification occurs. After heating and filling, Comparative Example 5 is subjected to steps such as freeze demoulding and drying, and finally a cosmetic powder block is prepared. However, due to the characteristics of gellan gum, pores are visible at the sharp angles of the fine relief on the surface of the prepared cosmetic powder block. In addition, in the process of transitioning from the high temperature conditions of filling to the frozen conditions of demoulding and drying in Comparative Example 5, the material is more likely to shrink, resulting in a lower drop resistance score of the cosmetic powder block than in Example 1. In addition, due to the high content of emulsifier in the cosmetic powder block formula of Comparative Example 5, the water resistance and sweat resistance of the obtained cosmetic powder block are poor. Specifically, as Figure 2 As shown, after flushing with water for 1 minute, the powder of Example 1 on the skin surface did not change significantly, while the powder of Comparative Example 5 was almost all taken away by water, indicating that the water resistance of the cosmetic powder block of Comparative Example 5 is far inferior to that of Example 1. From the anti-sweat score, the anti-sweat performance of the cosmetic powder block of Comparative Example 5 is also far inferior to that of Examples 1 to 12. In summary, the technical solution provided by the present application can realize the preparation of dense cosmetic powder blocks by a room temperature filling process, and the surface of the prepared cosmetic powder blocks is not easy to produce pores, has excellent density and anti-drop performance, has better water resistance and sweat resistance, and is not easy to remove makeup.

[0166] Comparative Examples 6 and 7 use hydroxyethyl acrylate / sodium acryloyldimethyl taurate copolymer and sodium polyacrylate to replace polyacrylate crosslinked polymer-6, respectively. Although hydroxyethyl acrylate / sodium acryloyldimethyl taurate copolymer, sodium polyacrylate, polyacrylate crosslinked polymer-6, sodium polyacryloyldimethyl taurate, ammonium acryloyldimethyl taurate / behenyl alcohol polyether-25 methacrylate crosslinked polymer in this application are all polyacrylate derivatives, they all have a crosslinked polymer network in structure and have some functional commonalities in conventional applications in cosmetics, but they still have many different properties based on their different monomer composition, molecular architecture, substituent type and physical form. Differences in dimensions such as hydrophilicity, thixotropy, temperature responsiveness, dispersion stability, etc. Comparative Examples 6 and 7 both have poor fluidity of the mixed material, cannot be filled at room temperature and pressure, and cannot form a stable emulsified system. The above comparison also illustrates that the present application uses at least one of polyacrylate cross-linked polymer-6, sodium polyacryloyldimethyl taurate, and ammonium acryloyldimethyl taurate / behenyl alcohol polyether-25 methacrylate cross-linked polymer as an adhesive to complete the molding process of the cosmetic powder block, and obtains unexpected technical effects. It is not a conventional choice or simple replacement of commonly used raw materials in cosmetics.

[0167] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or substitutions within the technical scope disclosed in the present application, and these modifications or substitutions should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims. For example, in accordance with the inventive concept of the present application, the technical solution of adding a small amount of thermoreversible polysaccharide (for example, the addition amount is less than 0.1wt%) to the raw material composition without affecting the effect of room temperature filling and reducing the amount of emulsifier should not be excluded from the protection scope of the present application.

Claims

1. A process for forming a cosmetic powder block, characterized in that: include: Mixing, including mixing the raw materials of the cosmetic powder block at 15-40° C. to obtain a mixed material body; Filling, including filling the mixed material into a mold at 15-40° C. and under normal pressure; Demolding and drying to obtain a cosmetic powder block; The mixed material body includes the following components in parts by mass: Adhesive: 0.02~1 part; Powder: 20~65 parts; Emollient: 0.5~35 parts; Preservative component: 0.05~3 parts; Emulsifier: 0.05~4 parts; Solvent: 40~80 parts; Wherein, the adhesive comprises at least one of polyacrylate cross-linked polymer-6, sodium polyacryloyldimethyl taurate, and ammonium acryloyldimethyl taurate / behenyl alcohol polyether-25 methacrylate cross-linked polymer.

2. The cosmetic powder block molding process according to claim 1, characterized in that: The adhesive includes polyacrylate crosspolymer-6.

3. The process for forming a cosmetic powder block according to claim 1, characterized in that: The mass fraction of the emulsifier is less than or equal to 4% of the total mass fraction of the mixture.

4. The cosmetic powder block molding process according to claim 1, characterized in that: The mass fraction of the emulsifier is less than or equal to 1% of the total mass fraction of the mixed material.

5. The cosmetic powder block molding process according to claim 1, characterized in that: The mass percentage of the solvent in the cosmetic powder block is less than 5%.

6. The cosmetic powder block molding process according to claim 1, characterized in that: The mass percentage of the solvent in the cosmetic powder block is less than 1%.

7. The cosmetic powder block molding process according to claim 1, characterized in that: The demoulding and drying include: drying after demoulding, or demoulding after drying.

8. The cosmetic powder block molding process according to claim 1, characterized in that: The drying includes at least one of freeze drying, microwave drying, heating drying, vacuum drying and supercritical fluid drying.

9. The cosmetic powder block molding process according to claim 1, characterized in that: Before the demoulding and drying, the molding process further includes pre-curing and / or pre-drying.

10. The cosmetic powder block molding process according to claim 9, characterized in that: The pre-curing includes freezing and curing the mixed material body after filling.

11. The cosmetic powder block molding process according to claim 10, characterized in that: The freezing and solidifying of the filled mixed material body comprises: placing the mixed material body in an environment of -120-0°C to solidify the mixed material body.

12. The cosmetic powder block molding process according to claim 11, characterized in that: The freezing and solidifying of the filled mixed material body comprises: placing the mixed material body in a liquid nitrogen tunnel at -120 to -70°C to solidify the mixed material body.

13. The cosmetic powder block molding process according to claim 12, characterized in that: The demoulding and drying include: After placing the mixed material body in a liquid nitrogen tunnel at -120 to -70°C to solidify the mixed material body, demolding the mixed material body, and then freeze-drying the mixed material body; Alternatively, the mixed material body is placed in a liquid nitrogen tunnel at -120 to -70°C to solidify the mixed material body, and then freeze-dried and demolded.

14. The cosmetic powder block molding process according to claim 10, characterized in that: The pre-drying comprises the step of removing part of the solvent from the mixed material body after filling.

15. The cosmetic powder block molding process according to claim 14, characterized in that: The step of removing part of the solvent from the mixed material after filling includes one or more of heating drying, microwave drying, vacuum drying, supercritical fluid drying, filter pressing, and suction.

16. The cosmetic powder block molding process according to claim 1, characterized in that: The powder is selected from at least one of mica, synthetic fluorphlogopite, talc, silica, boron nitride, bismuth oxychloride, barium sulfate, aluminum oxide, potassium sodium aluminum silicate, calcium aluminum borosilicate, calcium sodium borosilicate, starch and its derivatives, plastic microbeads and colorants; The emollient is selected from at least one of plant and animal fats and their derivatives, silicone oils and synthetic fats; The preservative component is selected from at least one of phenoxyethanol, parabens, chlorphenesin, potassium sorbate, sodium benzoate, caprylyl glycol, p-hydroxyacetophenone, ethylhexylglycerin, 1,2-hexanediol, caprylhydroxamic acid, 1,2-pentanediol, glyceryl caprylate and cymene; The emulsifier is selected from emulsifiers having a hydrophilic-lipophilic balance (HLB) value greater than 6; The solvent is selected from water or a mixture of water and an organic solvent.

17. The cosmetic powder block molding process according to claim 16, characterized in that: The emulsifier having an HLB value greater than 6 is selected from at least one of Tween 20, Tween 40, Tween 60, Tween 80, PEG-12 polydimethylsiloxane, polyglyceryl-10 myristate, polyglyceryl-10 laurate and polyglyceryl-10 dioleate; The organic solvent is selected from at least one of ethanol, isopropanol, butanol and polyols.

18. The cosmetic powder block molding process according to claim 1, characterized in that: The mold is made of silicone, rubber or metal.

19. The cosmetic powder block molding process according to claim 18, characterized in that: The rubber includes at least one of TPR, TPE, silicone rubber and natural rubber.

20. The cosmetic powder block molding process according to claim 1, characterized in that: The mold includes at least one cavity having an opening.

21. The cosmetic powder block forming process according to claim 20, characterized in that: The bottom of the chamber has a three-dimensional pattern.

22. The process for forming a cosmetic powder block according to any one of claims 1 to 21, characterized in that: The mixed material body also includes an active substance.

23. The cosmetic powder block forming process according to claim 22, characterized in that: The active substance includes at least one of polypeptide active substances, astaxanthin, and vitamin A alcohol.

24. A cosmetic powder block, characterized in that: The cosmetic powder block is prepared by the molding process of any one of claims 1 to 23.

Citation Information

Patent Citations

  • Cosmetic with brightening effect and mousse texture and preparation method thereof

    CN107648072A

  • Azelaic acid gel as well as preparation method and application thereof

    CN115154411A

  • Stable aqueous dispersion system of iron oxide red powder and preparation method of stable aqueous dispersion system

    CN115670948A

  • Preparation process of powder product

    CN117205112A

  • Preparation method of blocky powder cosmetic and blocky powder cosmetic

    CN119235667A

Cited By

  • Pearlescent powder block type cosmetic and preparation method thereof

    CN121221467A